2018
DOI: 10.1038/s41598-018-30502-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional study of a mild allele of SlDELLA gene conferring the potential for improved yield in tomato

Abstract: Parthenocarpy, or pollination-independent fruit set, is an attractive trait for fruit production and can be induced by increased responses to the phytohormone gibberellin (GA), which regulates diverse aspects of plant development. GA signaling in plants is negatively regulated by DELLA proteins. A loss-of-function mutant of tomato DELLA (SlDELLA), procera (pro) thus exhibits enhanced GA-response phenotypes including parthenocarpy, although the pro mutation also confers some disadvantages for practical breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 58 publications
(69 reference statements)
2
30
0
Order By: Relevance
“…Consistent with this, the silencing of the SlDELLA gene in tomato resulted in small, facultative parthenocarpic fruits with an elongated shape (Martí et al, 2007). The procera ( pro ) mutant, which carries a point mutation in the GRAS region of SlDELLA , has also very strong parthenocarpic capacity and shows enhanced growth of preanthesis ovaries (Jones, 1987; Carrera et al, 2012; Shinozaki et al, 2018c). The parthenocarpic capacity of pro is mainly associated with changes in the expression of genes involved in GA and auxin pathways (Carrera et al, 2012).…”
Section: Hormonal Regulation Of the Development And Ripening Of Tomatmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, the silencing of the SlDELLA gene in tomato resulted in small, facultative parthenocarpic fruits with an elongated shape (Martí et al, 2007). The procera ( pro ) mutant, which carries a point mutation in the GRAS region of SlDELLA , has also very strong parthenocarpic capacity and shows enhanced growth of preanthesis ovaries (Jones, 1987; Carrera et al, 2012; Shinozaki et al, 2018c). The parthenocarpic capacity of pro is mainly associated with changes in the expression of genes involved in GA and auxin pathways (Carrera et al, 2012).…”
Section: Hormonal Regulation Of the Development And Ripening Of Tomatmentioning
confidence: 99%
“…The parthenocarpic capacity of pro is mainly associated with changes in the expression of genes involved in GA and auxin pathways (Carrera et al, 2012). A new SlDELLA mutant containing a single nucleotide substitution, procera2 ( pro2 ), has been recently identified and shows a potential for high fruit yield in both optimal and unfavorable growing conditions due to its facultative parthenocarpic capacity (Shinozaki et al, 2018c). Parthenocarpy is indeed an attractive trait for fruit production (Shinozaki et al, 2018c).…”
Section: Hormonal Regulation Of the Development And Ripening Of Tomatmentioning
confidence: 99%
“…In conclusion, this study identified a novel tomato mutant showing parthenocarpy and this was caused by the loss of function in the gene encoding a receptor kinase gene designated as SPFF . The parthenocarpic variety potentially shows improved fruit productivity due to increased fruit set efficiency (Shinozaki et al, 2018a), although the spff produced delayed growth, smaller mature fruits and reduced yield compared to WT (Figure 5). Such unfavorable traits render this mutant less attractive for breeding application, but it would be interesting to identify hypomorphic (weaker) alleles of spff carrying less detrimental phenotypes through screening from TILLING populations or genome editing approaches (Okabe et al, 2011; Shimatani et al, 2017), and investigate their potentials for impact on breeding application.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in Brix value has been reported in some parthenocarpic tomato lines (Carmi et al, 2003; Medina et al, 2013). Higher Brix index and lycopene content have also been reported in the procera-2 parthenocarpic mutant, a novel allele of SlDELLA (Shinozaki et al, 2018).…”
Section: Discussionmentioning
confidence: 85%